Intermediate monocytes are increased in enthesitis‐related arthritis, a category of juvenile idiopathic arthritis. (28th October 2016) - Gaur, P.; Myles, A.; Misra, R.; Aggarwal, A.
Summary: Microarray of peripheral blood (PB) and synovial fluid mononuclear cells (PBMC, SFMC) of patients with juvenile idiopathic arthritis–enthesitis‐related arthritis (JIA‐ERA) has shown the involvement of monocytes. On the basis of CD14 and CD16 expression, monocytes are classified as classical, intermediate and non‐classical. In response to Toll‐like receptor (TLR) stimulation, intermediate monocytes produce proinflammatory cytokines and play a role in inflammatory diseases. Therefore, we have studied the microarray profile of monocytes, the frequency of their subsets and cytokine production. Monocyte‐specific microarray analysis was performed in six healthy controls' PBMC and six patients' PBMC and SFMC using Illumina chips WG12. Monocyte subsets were assessed in 46 patients with JIA‐ERA and 17 healthy controls and 17 disease controls by flow cytometry. Interleukin (IL)−23 and tumour necrosis factor (TNF) levels were measured in culture supernatants of eight controls and seven patients' PBMC/SFMC with/without lipopolysaccharide (LPS) stimulation. Cytokine‐producing intermediate monocytes were assessed by flow cytometry. Genes related to antigen presentation, cytokine signalling and TLR pathway were regulated differentially in PB and synovial monocytes of patients with JIA‐ERA. Key genes of intermediate monocytes, such as CLEC10A and MARCO, were expressed three‐ to fourfold more in JIA‐ERA. In PB, the frequency of intermediate monocytes was significantly higher in JIA‐ERA (4·90% ± 3·5) compared to controls (1·8% ± 1·06; P  < 0·001). Patients' synovial cells also had more intermediate monocytes compared to PB (11·25% ± 11·32, 5·9% ± 4·8; P  = 0.004). Intermediate monocytes are the major producers of IL‐23. Thus, intermediate monocytes may play an important role in JIA‐ERA, possibly by producing cytokines, and contribute to joint inflammation. Abstract : Monocyte specific transcriptome analysis in ERA revealed increased expression of genes related to intermediate monocytes. Frequency of intermediate monocytes was increased in PB and SF of these patients. Intermediate monocytes produced IL‐23, in response to TLR stimulation which may help in perpetuating inflammation in ERA by inducing IL‐17 production.